Plan de intervención psicoeducativo basado en la teoría de branden para fortalecer la autoestima en los estudiantes de quinto año de educación básica paralelo a, de la escuela 18 de noviembre, 2017-2018. - Mendoza Jimenez, Karen Elizabeth (2018)
Present investigation be about A psycho-educative intervention plan based in the Branden theory to enforce self-steem in students of the fifth-year class "A" of the "18 de Noviembre" school, the main objective was to; implement a psycho-educative intervention plan based in the Branden theory to enforce self-stem in students. Research was a descriptive study, cross sectional with a pre-experimental design, methods used were: scientific, deductive, inductive, analytic, synthetic and historical – logical. Instrument applied was the Coopersmith Selfsteem Inventory, to know the level of self-stem students showed. Sample was of 33 students from the fifth grade, sample was chosen by non-probabilistic sampling method. As a product of this research is concluded that the students self-steem was significantly improved because in the initial diagnostic most of students (54.5%) was found that had a low self-stem and after the application of the psycho-educative program their self-stem was raised to a "high" level, validating the intervention proposal, hence is recommended to teacher continue the usage of this ludic techniques to keep improving his/her students self-stem.